Endotrophin is significantly associated with disease severity and increased risk of adverse outcome in HFpEF but not in HFrEF patients. (14th October 2021) - Reese-Petersen, A.L; Gonzalez, A; Lopez, B; Ravassa, S; Karsdal, M; Genovese, F; Diez, J
Abstract: Introduction: The global burden of heart failure (HF), with either reduced (HFrEF) or preserved (HFpEF) ejection fraction, has increased dramatically over the past years, and HFpEF is projected to become the dominant type of HF. Fibrogenesis, promoted by fibroblast activity, plays an important role in the pathology of HF regardless of subtype, causing impaired cardiac function. Endotrophin is a bioactive molecule released from collagen type VI during its maturation, and it is a marker of fibroblast activity. The aim of this post-hoc analysis was to confirm the previously observed prognostic potential of endotrophin (measured by PRO-C6) for adverse outcome in HFpEF and to test its prognostic abilities in HFrEF. Methods: 234 patients with hypertension and either HFrEF (30.3%) or HFpEF (69.7%) were included for analysis. 43.2% were NYHA Class II, 52.5% NYHA Class III and 2.5% NYHA Class IV. 53.4% of patients had a previous history of atrial fibrillation. The cohort did not include diabetic patients. Cardiac function was assessed by echocardiography and standard clinical measures, including left ventricle ejection fraction (EF), blood pressure (BP) and measurement of N-terminal natriuretic brain-peptide (NT-proBNP). Circulating endotrophin was quantified at baseline in serum by means of an enzyme-linked immunosorbent assay, PRO-C6. Results: PRO-C6 levels increased significantly with disease severity in HFpEF patients (NYHA Class III vs II, p=0.0003), but not in HFrEF patients (NYHA Class III vs II, p=0.33). In HFpEF patients, PRO-C6 was able to discriminate between patients that were hospitalized for HF (AUC=0.69, p<0.001), died from cardiovascular (CV) causes (AUC=0.74, p<0.001), or by any other cause (AUC=0.73, p<0.001). PRO-C6 was not associated with none of these outcomes in HFrEF patients (AUC=0.56, p=0.42; AUC=0.53, p=0.73; AUC=0.56, p=0.53, respectively). Adding PRO-C6 to a risk prediction model containing age, sex, body mass index and systolic BP significantly increased the discriminatory power of the model for mortality (deltaAUC=0.037, p=0.04). When looking at patients stratified in PRO-C6 tertiles, patients in the upper tertile had a significantly higher risk of mortality (p<0.0001, hazard ratios 3 vs 1=4.1, 3 vs 2=3.5, respectively) and HF hospitalization (p<0.0001, hazard ratio 3 vs 1=4.4, 3 vs 2=1.6, respectively) compared to tertiles 1 and 2. Conclusion: In this population of hypertensive HF patients, circulating endotrophin, measured by PRO-C6, was increased with increasing disease severity, and associated with a higher risk of adverse outcome in HFpEF, but not in HFrEF patients. The data presented here suggest a potential role of endotrophin in HFpEF pathophysiology and further underline the differences between HFpEF and HFrEF. These data confirm previous observations, and strengthen the usefulness of endotrophin, measured by the PRO-C6 biomarker, as a prognostic tool aiding in assessment of HFpEF patients. Funding Acknowledgement: Type of funding sources: None.